Exact exchange Kohn-Sham formalism applied to semiconductors - Städele, Martin; Moukara, M.; Majewski, Jacek; Vogl, Peter; Görling, Andreas (Physical Review B, 1999)
We present a Kohn-Sham method that allows one to treat exchange interactions exactly within density-functional theory. The method is used to calculate lattice constants, cohesive energies, Kohn-Sham eigenvalues, dielectric functions, and effective masses of various zinc-blende semiconductors (Si, Ge, C, SiC, GaAs, AlAs, GaN, and AlN). The results are compared with values obtained within the local-density approximation, generalized gradient approximations, the Krieger-Li-Iafrate approximation for the Kohn-Sham exchange potential, and the Hartree-Fock method. We find that the exact exchange formalism, augmented by local density or generalized gradient correlations, yields both structural and optical properties in excellent agreement with experiment. Exact exchange-only calculations are found to lead to densities and energies that are close to Hartree-Fock values but to eigenvalue gaps that agree with experiment within 0.2 eV. The generalized gradient approximations for exchange yield energies that are much improved compared to local-density values. The exact exchange contribution to the discontinuity of the exchange-correlation potential is computed and discussed in the context of the band-gap problem. ©1999 The American Physical Society.